Conversion of a Fused or Ankylosed Hip to Total Hip Arthroplasty: Is the Direct Anterior Approach in the Lateral Decubitus Position an Ideal Solution? - Dong, Jiale; Kong, Lingtong; Zhang, Siming; Shang, Xifu; Wang, Jiaxing; Zhang, Xianzuo; Zhu, Chen (Frontiers in Surgery, 2022)
Background: Total hip arthroplasty (THA) using the direct anterior approach (DAA) is becoming increasingly popular due to its potential benefits over the posterolateral approach (PLA). However, few studies have compared the efficacies of these two surgical approaches in hip fusion treatment. This study compared early clinical direct anterior and posterolateral THA outcomes in hip fusion treatment. Methods: Here, 127 hips (65 DAA, 62 PLA) were retrospectively evaluated. Early postoperative functional outcomes of DAA and PLA groups were assessed using Harris score and Oxford Hip Score (OHS) and standard anteroposterior hip radiographs. Surgical characteristics, perioperative results, and complications within 6 months postoperatively were recorded. Results: Though baseline values were similar, Harris and OHS scores were better in the DAA group than in the PLA group at 1 and 3 months postoperatively. The average cup anteversion angle was significantly greater in the DAA group than in the PLA group (12.7° versus 11.1°). More hips undergoing DAA were successfully orientated in both inclination and anteversion angles (46 versus 32). Early postoperative hip function predictors were preoperative fused hip position, surgical approach, and range of motion. DAA was associated with reduced postoperative blood loss and shorter hospital stays. Furthermore, 14 versus 8 complications occurred in the DAA versus PLA group. Lateral femoral cutaneous nerve injuries were observed in eight hips (12.3%) of the DAA group. Conclusion: For fused or ankylosed hips, THA using DAA in the lateral decubitus position may result in excellent prosthesis positioning and faster postoperative recovery throughout early follow-up versus PLA.